Traffic signal timing manual (U.S. Department of Transportation, Federal Highway Administration, 2008)
This report serves as a comprehensive guide to traffic signal timing and documents the tasks completed in association with its development. The focus of this document is on traffic signal control principles, practices, and procedures. It describes the relationship between traffic signal timing and transportation policy and addresses maintenance and operations of traffic signals. It represents a synthesis of traffic signal timing concepts and their application and focuses on the use of detection, related timing parameters, and resulting effects to users at the intersection. It discusses advanced topics briefly to raise awareness related to their use and application.
"Publication no. FHWA-HOP-08-024."
"June 2008."
Title from title screen (viewed on June 27, 2011).
Performed by Kittelson & Associates, Inc.
Keywords: Traffic signs and signals -- Handbooks, manuals, etc.; Electronic traffic controls -- Handbooks, manuals, etc.; Traffic flow -- Management.; elektronické knihy; electronic books